Analisis Akurasi Indeks Pont pada Pasien Maloklusi RSGM USAKTI - Marietha Marylin Anrose Manalu, Vetrycia; Halim, Himawan (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: The Pont Index is utilized as a method to predict the arch width of the maxilla in orthodontic treatment. An evaluation of the Pont Index in malocclusion patients at RSGM-P USAKTI is necessary to assess its relevance in planning and achieving successful orthodontic treatments. Objectives: This study aims to determine the accuracy of the Pont Index in malocclusion patients at RSGM-P USAKTI.. Methods: This research employed a descriptive-analytic design with a sample of 30 maxillary dental models from malocclusion patients at RSGM-P USAKTI during the 2022-2023 period. Measurements were conducted using a vernier caliper to determine the premolar and molar ratios based on the mesiodistal width of the maxillary incisor, interpremolar distance, and intermolar distance. Data analysis was performed using the Shapiro-Wilk test and One-Sample Test with SPSS software. Results: The data analysis revealed that the average premolar and molar ratios were significantly different from the standard Pont Index values (0,80 for premolar and 0,64 for molar). This indicated that the Pont Index cannot be applied to predict dental arch width in patients with malocclusion at RSGM-P USAKTI Conclusion: The Pont Index is not relevant for use in the orthodontic treatment planning for the patients with malocclusion at RSGM-P USAKTI.